Code Mixing Used by Youtuber - Nessie Judge’s Entitled “Pekerjaan-Pekerjaan yang Sudah Punah karena Teknologi” - Abdulloh, Abdulloh; Ilahi, Wahyu; Muslim, Ikhwan; Sarsono, Sarsono; Basuki, Slamet (STIBA IEC JAKARTA, 2024)
The blending of two or more languages or linguistic subtypes in speech is known as code mixing. Code mixing widely used either in written or spoken language. Social media nowadays mostly use spoken form especially YouTube. The purposes of the research are to investigate the use of code mixing in Nessie Judge’s videos and try to describe the type of code mixing used by the youtuber. Descriptive qualitative method used to gain the data analysis. The code mixing then, analyzed into two types: intra sentential and intra lexical code mixing. Type of intra sentential then classified into three kinds: interrogative, declarative, and imperative. The intra sentential and intra lexical then classified into five levels: word, phrase, clause, idiom and baster. The result shows that there are 24 types of intra sentential and 1 type of intra lexical. From the sub type of sentential found 23 types of declarative, 1 interrogative, and no imperative type. While the level of code mixing found 12 words level, 5 phrases level, no idiom level, 8 clauses level, and 2 basters level.